Earnings, Schooling and Vocational Education and Training - Stromback, Thorsten (The Centre for Labour Market Research, Curtin Business School, Curtin University of Technology, 2010)
Young persons who do not go on to university face two main educational choices; whether to complete Year 12 and/or whether to undertake a vocational (VET) qualification. These two choices are independent. Both early leavers and completers may subsequently obtain a VET qualification. However, the parametric models that are commonly used to analyse the causal effect of education presume that educational attainments form an ordered sequence. This has the effect of restricting the effects of educational attainments on earnings. This paper departs from this restrictive approach. It estimates the effect of Year 12 completion and VET qualifications on early career earnings using both a single and multiple treatment-effect approach. By using matching methods to estimate these effects, it also allows for the effects of educational qualifications differ between persons. It is found that neither completion of Year 12 nor a VET qualification has an effect on early career earnings over and above the forgone experience.